Changes in the user profiles of HIV pre-exposure prophylaxis (PrEP) before and after PrEP reimbursement. Issue 9 (September 2022) - Ahaus, Patrick; Schmidt, Axel J.; Skaletz-Rorowski, Adriane; Uhrmacher, Mona; Serova, Katja; Kayser, Arne; Wach, Janet; Nambiar, Sandeep; Brockmeyer, Norbert H.; Potthoff, Anja
Abstract: Background: In Germany, oral HIV pre-exposure prophylaxis (PrEP) was licensed in 2016. Health insurances have been covering the costs since 09/2019. This study compares the sociodemographic profiles of PrEP users before and after PrEP re-imbursement. Methods: Participants were recruited in a cross-sectoral sexual health centre in Germany. baseline data were compared for 139 vs 138 individuals starting PrEP from 10/2017–12/2018 (pre-reimbursement cohort) and 09/2019–3/2020; respectively. The pre-reimbursement cohort was further analysed with respect to sexual behaviour and incident sexually transmitted infections (STIs). Results: There were no significant differences in the sociodemographic characteristics between the two cohorts. Almost all PrEP users were men-who-have-sex-with-men (MSM). Before reimbursement, fewer individuals used PrEP on a daily base, and more had used PrEP prior to enrolment. During follow-up (pre-reimbursement cohort), the number of sexual and condomless intercourse partners increased, so did the proportion engaging in Chemsex. Incidences of infections with C.trachomatis, N.gonorrhoeae, M.genitalium, and T.pallidum were 45.2; 36.8; 30.1; and 9.2, respectively, per 100 person-years. Conclusion: The goal to make PrEP available to a broader range of people with the covering of costs was only partially reached. Medically supervised use is important to detect and treat STIs.